Classification of Automatic Subtitling Tools. A Proposal - Cristina VARGA (Scientific Bulletin of the Politehnica University of Timişoara: Transactions on Modern Languages)
This article aims to provide a deeper understanding of the automatic subtitling tools that are currently being used and of their context of application. Based on the assumption that AVT, in general, and subtitling, in particular, are undergoing fundamental changes, it is our aim to analyse the range of tools that allow AVT translators to enhance their productivity and their efficiency. For this purpose, we have analysed 40 different automatic subtitling tools, currently available and accessible on Internet. Through this analysis, it has been possible to observe the main features of these tools and observe their functioning. Therefore, different criteria have been established in order to systemize this extensive inventory based on which 23 categories of software dedicated to automatic subtitling have been identified. These categories have been illustrated with examples. In this study, the aim is to provide a more accurate and more systematic understanding of automated subtitling programs. The paper is addressed to AVT professionals as well as to teachers and students having an interest in the state-of-the-art of automated subtitling.